The processing of images in Parkinson’s disease - Corkidi B., Gabriel (Revista Mexicana de Ingenieria Biomedica, 1991)
A digital image processing system was developed, specifically designed for the interactive analysis of histological preparations, based on an innovative semi-automatic analysis methodology of preparations of macroscopic dimensions (6.4 x 6.4 cm). This methodology allows to combine in real time the macroscopic information (for example the areas of interest) with the analysis at high amplification. The program generalizes these concepts to functions such as object counting, morphometry and optical density measurement (application in histo-autoradiography). The system allows the edition of high resolution cartographic documents, the synthesis of parametric images and the creation of result files. In this work, the evaluation of the system was carried out in a particular application: comparative study of different types of dopaminergic neurons of the normal and pathological human ventral mesencephalon (parkinson’s disease). This study allowed us to quantify and localize the preferentially injured neurons in different neuro-anatomical regions in the parkinsonian subject. It was noted in the course of this study, that a new parameter would seem to be correlated with the death of these neurons: the orientation of neuronal bodies in substantia nigra. This work was carried out in the company BIOCOM (Les Ulis, FRANCE) in close collaboration with unit 289 of INSERM (Institut de Santé et de Recherche Médicale, Paris, FRANCE).